A LOW-COST PAPER-BASED MICROFLUIDIC IMPEDIMETRIC DEVICEC FOR THE DETECTION OF WATER HARDNESS - Migelhewa Nidarsha Kaumal; Niroodha Pitawela (Tanjungpura University, 2021)
A microfluidic paper-based impedimetric device was developed as a water hardness sensor. This device is capable of performing the analysis with a sample volume of few microliters with no prior treatments. A phenol-formaldehyde graphene electrode modified with ethylenediaminetetraacetate was used as the working electrode. Ag pseudo reference and carbon electrodes were used to fabricate the device. Current simultaneous metal ion detection sensors are based on complex and expensive electrode setups. The proposed inexpensive, quick and portable device is capable of detecting Ca2+ and Mg2+ simultaneously. Electrode double layer-based charge transfer resistance and the maximum negative imaginary impedance produced a linear correlation with each metal ion concentration. The calculated limits of detection for Ca2+ and Mg2+ were 0.31 and 0.24 ppm, respectively. A set of samples containing Ca2+ and Mg2+ with a hardness of 2 ppm (as calcium carbonate) were used to test the device. The proposed tool is suitable as a semi-quantitative device for the determination of hardness in water.